Receptor-Interacting Protein Kinase 3 Suppresses Mitophagy Activation via the Yes-Associated Protein/Transcription Factor EB Pathways in Septic Cardiomyopathy - Zhu, Pingjun; Chen, Yangxiaocao; Wang, Junyan; Lin, Geng; Wang, Runsheng; Que, Yifan; Zhou, Jin; Xu, Guogang; Luo, Jiang; Du, Yingzhen (Frontiers in Cardiovascular Medicine, 2022)
Mitophagy, known as the main mechanism of mitochondrial quality control, determines the pathophysiology of septic cardiomyopathy, although the precise regulatory mechanisms remain elusive. Data from the present study suggested that receptor-interacting protein kinase 3 (RIPK3) expression could be enhanced in response to lipopolysaccharide (LPS) challenge. Upregulated RIPK3 expression was accompanied by severe cardiac injury and cardiac dysfunction. Further examination revealed that elevated RIPK3 expression subsequently inhibited the Yes-associated protein (YAP) pathway, which was accompanied by reduced transcription factor EB (TFEB) expression. Inhibition of TFEB would reduce mitophagy, which ultimately induced cardiomyocyte death under LPS challenge. In contrast, loss of RIPK3 induced the YAP/TFEB/mitophagy pathway alleviated the sensitivity of cardiomyocytes to LPS-induced cytotoxicity. Collectively, the RIPK3/YAP/TFEB axis was confirmed to be responsible for the pathogenesis of septic cardiomyopathy by inhibiting mitophagy. These findings have potential significance for the progression of new approaches to the treatment of septic cardiomyopathy.